2011
DOI: 10.1021/ie101423v
|View full text |Cite
|
Sign up to set email alerts
|

Production of Reactive Oxygen Species by Photoactive Anthraquinone Compounds and Their Applications in Wastewater Treatment

Abstract: 2-Anthraquinone sulfonate (2-AQS) was found to exhibit an abnormally high singlet-oxygen quantum yield in aqueous solution after UVA irradiation based on a widely used testing method for singlet oxygen. To discover the cause of the abnormal results, several possible reactive oxygen species were also measured in the system. Results revealed that 2-AQS and two other similar compounds produced singlet oxygen, hydroxyl radicals, and superoxide, so-called reactive oxygen species (ROS), under UVA exposure. The produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 37 publications
1
70
0
2
Order By: Relevance
“…Singlet oxygen ( 1 O 2 ) is a reactive oxygen species that has been reported countless times in the literature as an important tool to induce oxidative damage in biological systems (24)(25)(26). As 1 O 2 is the excited form of molecular oxygen, with a finite lifetime of 10 À6 -10 À3 s in solution (27,28), and is highly reactive, it has been used in a broad range of applications including organic chemical synthesis (29)(30)(31), wastewater treatment (28,32,33) and photodynamic therapy (34)(35)(36). Interestingly, it has been shown that the metal enhancement effect is not limited to fluorescence, and enhancement of both 1 O 2 production, and phosphorescence quantum yield have been observed (12,(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Singlet oxygen ( 1 O 2 ) is a reactive oxygen species that has been reported countless times in the literature as an important tool to induce oxidative damage in biological systems (24)(25)(26). As 1 O 2 is the excited form of molecular oxygen, with a finite lifetime of 10 À6 -10 À3 s in solution (27,28), and is highly reactive, it has been used in a broad range of applications including organic chemical synthesis (29)(30)(31), wastewater treatment (28,32,33) and photodynamic therapy (34)(35)(36). Interestingly, it has been shown that the metal enhancement effect is not limited to fluorescence, and enhancement of both 1 O 2 production, and phosphorescence quantum yield have been observed (12,(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated hydroperoxyl radicals then react with another of its species to form hydrogen peroxide and molecular oxygen. The details of this mechanism are much more complex than presented here and are described comprehensively elsewhere [26, 40]. A kinetic model to describe the generation of H 2 O 2 based on this reaction mechanism is proposed in equation (1).…”
Section: Resultsmentioning
confidence: 99%
“…The AQS could have been excited to the singlet state under UV light irradiation and then efficiently intersystem‐crossed to triplet states for diaryl ketone, which could have easily abstracted a hydrogen atom from a weak CïŁżH bond or other hydrogen donor to form a ketyl radical 28–30. The reaction of ketyl radicals with oxygen could then produce active superoxide, peroxide, and hydroxyl radicals, which were capable of degrading pollutants and inactivating bacteria.…”
Section: Resultsmentioning
confidence: 99%